2007
DOI: 10.1074/jbc.m700785200
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cell Proliferation Is Inhibited by BAD

Abstract: Recent studies on BCL2 family proteins suggest that members of the proapoptotic arm have functions distinct from apoptosis induction. BID has been shown to have a role in the DNA damage response (1), and BAX and BID take part in homologous recombination (2). A prosurvival role for BAD was demonstrated in murine neuronal cells (2), and metabolic functions of BAD were described in mice (3). Growth regulation by BCL2 family proteins has been previously reported, although the mechanisms are poorly defined (4 -6). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 39 publications
5
38
0
1
Order By: Relevance
“…cyclin D1 has a rate-limiting role in G 1 -S phase transition. Both transgenic mouse models and clinical studies indicate a pivotal role for cyclin D1 in normal and malignant cell growth, particularly in breast cancer [36] . In our experiments, Western blot analysis showed that DKK-1 was able to downregulate the expression of c-Myc and cyclin D1 (Figure 3), suggesting that c-Myc and cyclin D1 are downstream effectors of DKK-1.…”
Section: Discussionmentioning
confidence: 99%
“…cyclin D1 has a rate-limiting role in G 1 -S phase transition. Both transgenic mouse models and clinical studies indicate a pivotal role for cyclin D1 in normal and malignant cell growth, particularly in breast cancer [36] . In our experiments, Western blot analysis showed that DKK-1 was able to downregulate the expression of c-Myc and cyclin D1 (Figure 3), suggesting that c-Myc and cyclin D1 are downstream effectors of DKK-1.…”
Section: Discussionmentioning
confidence: 99%
“…The alteration of the balance may lead to the leakage of cytochrome c and the formation of apoptosome which subsequently activates the caspase cascade culminating in apoptosis (2). BAD (BCL-2 antagonist of cell death) is a BH3-only proapoptotic BCL-2 family protein and plays a critical role in radiation-induced apoptosis (3)(4)(5). Under physiological conditions, anti-apoptotic BCL-2 family proteins promote cell survival by sequestering the pro-apoptotic BCL-2 proteins such as BAX and BAK (6).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, paclitaxel treatment did not induce mitochondrial translocation of Bad (Figure 4a, compare green arrows). Furthermore, because nuclear localization of Bad has also been reported (Fernando et al, 2007), we used a more specific subcellular fractionation method to examine whether paclitaxel treatment affected accumulation of Bad to the nucleus. As shown in Figure 4b, again staurosporine, but not paclitaxel treatment, stimulated Bad translocation to mitochondrial-enriched membrane fractions, but there was no detectable nuclear accumulation of Bad under any of the conditions tested.…”
Section: Resultsmentioning
confidence: 99%